Low incidence of plastic ingestion among three fish species significant for human consumption on the island of Newfoundland, Canada. (April 2019) - Liboiron, Max; Melvin, Jessica; Richárd, Natalie; Saturno, Jacquelyn; Ammendolia, Justine; Liboiron, France; Charron, Louis; Mather, Charles
Abstract: This study reports the first baselines of plastic ingestion for three fish species that are common commercial and sustenance food fish in Newfoundland. Species collections occurred between 2015 and 2016 for Atlantic cod ( Gadus morhua ), Atlantic salmon ( Salmo salar ), and capelin ( Mallotus villosus ). The frequency of occurrence (%FO) of plastic ingestion for both Atlantic salmon ( n  = 69) and capelin ( n  = 350) was 0%. Of the 1010 Atlantic cod individuals collected over two years, 17 individuals had ingested plastics, a %FO of 1.68%. This is the only multi-year investigation of plastic ingestion in Atlantic cod for the Northwest Atlantic, and the first baseline of plastic ingestion in Atlantic salmon and capelin on the island of Newfoundland. Considering the ecological, economic, and cultural importance of these fish species, this study is the beginning of a longitudinal study of plastic ingestion to detect any future changes in contamination levels. Highlights: Ingestion rate (%FO) of plastics in Atlantic cod is 1.68%. Ingestion rate (%FO) of plastics in Atlantic salmon and capelin is 0%. First study of plastic ingestion rates in Atlantic salmon and capelin Multi-year baseline of plastic ingestion in Atlantic cod in the Northwest Atlantic Plastic ingestion rates for three food fish species in Newfoundland, Canada, are low.